2021
DOI: 10.3389/fenvs.2021.790560
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Reduce the Negative Effects of Litter-Derived Plant Secondary Metabolites on Nematodes in Soil

Abstract: Microplastics and plant litter are ubiquitous in the soil environment, and both materials can influence soil properties and biota. Plant litter releases secondary metabolites (e.g., phenolic compounds) during the decomposition process, including chemical compounds active in plant defense. Effects of microplastics and plant litter on soil biota have been studied independently but we have limited information about the combined effects of both sources of chemicals. Here, we specifically focused on the interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Soil organisms also play essential ecological roles in the decomposition process, such as nematodes, which can ingest litter fragments and break them down into simple inorganic substances. However, the plant secondary metabolites derived from litter influenced by MNP may have potentially negative effects on soil nematodes, inhibiting their decomposition of litter [81].…”
Section: The Impact Of Mnp On the Decomposition Of Plant Littermentioning
confidence: 99%
“…Soil organisms also play essential ecological roles in the decomposition process, such as nematodes, which can ingest litter fragments and break them down into simple inorganic substances. However, the plant secondary metabolites derived from litter influenced by MNP may have potentially negative effects on soil nematodes, inhibiting their decomposition of litter [81].…”
Section: The Impact Of Mnp On the Decomposition Of Plant Littermentioning
confidence: 99%
“…While some animal SMs originate internally, most are diet-derived, often through plant consumption . Ingested SMs, whether directly or via MPs following adsorption, can influence metabolic rates, nutrient digestibility, and energy expenditure based on type and quantity . Moreover, animals exploit SMs as a strategy to counter challenges that disturb homeostasis due to their bioactive attributes, like antioxidants countering oxidative damage .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large MP size, nematodes could not ingest them and negligible effects were assessed on both C. elegans and V. fischeri endpoints, unless the concentration of simazine increased to 15 Kiyama et al [188] also suggested that C. elegans could discriminate plastics based on size. A different approach established that MPs could reduce the negative impacts on the nematode C. elegans of toxic compounds present in plant litter because MPs could effectively retain the toxic phenolic compounds [189]. Furthermore, Lei et al [190] showed that the effect of MPs on C. elegans was size-dependent, by comparing PS at 100-500 nm and 1-5 µm.…”
Section: Terrestrial Ecosystemsmentioning
confidence: 99%